Ten questions concerning the built environment and mental health. (15th May 2019) - Hoisington, Andrew J.; Stearns-Yoder, Kelly A.; Schuldt, Steven J.; Beemer, Cody J.; Maestre, Juan P.; Kinney, Kerry A.; Postolache, Teodor T.; Lowry, Christopher A.; Brenner, Lisa A.
Abstract: Most people spend the majority of their lives indoors. Research over the last thirty years has focused on investigating the mechanisms through which specific elements of the built environment, such as indoor air quality, influence the physical health of occupants. However, similar effort has not been expended in regard to mental health, a significant public health concern. One in five Americans has been diagnosed with a mental health disorder in the past year, and, in the United States, the number of suicide deaths are similar to the number of deaths due to breast cancer. Increases in mental health disorders in Western societies may be due, in part, to increased systemic inflammation, secondary to decreased exposures to a diverse microbial environment (i.e., the hygiene hypothesis, "Old Friends" hypothesis, "missing microbes" hypothesis, or biodiversity hypothesis), as well as increased environmental exposures that lead to chronic low-grade inflammation. In this review, we provide an assessment that integrates historical research across disciplines. We offer ten questions that highlight the importance of current lessons learned regarding the built environment and mental health, including a potential role for the microbiome of the built environment to influence mental health. Suggested areas for future investigation are also highlighted. Highlights: Design of the built environment in the build environment rarely has intentional design elements to improve mental health. Knowledge is needed in the built environment in regards to occurrence, severity, and treatment response of mental illness. Evidence-based research for policy makers need clear guidance and incentives to benefit the mental health of occupants.